Mutation analysis of B-RAF gene in human gliomas - Basto, Diana (2005)
The RAS/RAF/MEK/ERK kinase pathway is pivotal in the transduction of mitogenic stimuli from activated growth factor receptors, which regulates cell proliferation, survival, and differentiation. Up-regulation of this pathway due to RAS mutations is found in approximately 30% of human tumors. Recently, activating mutations of B-RAF were identified in a large proportion of human cancers. Gliomas are the most frequent primary central nervous system tumors and the molecular mechanisms that underlie the development and progression of these tumors are far from being completely understood. The purpose of this study was to clarify the incidence of B-RAF mutations and their possible relation with tumor progression in a series of 82 human gliomas, including 49 astrocytic and 33 oligodendroglial tumors. The analysis of B-RAF hotspot regions, exons 11 and 15, showed presence of B-RAF mutations in only 2 out of 34 (6%) glioblastomas, and absence in the remaining histological types. Both mutations were located in the hotspot residue 600 (V600E) at exon 15, which leads to constitutive B-RAF kinase activity. These data suggest that activating mutations of B-RAF are not a frequent event in gliomas; nevertheless, when present they are associated with highgrade malignant lesions.